Simplifying the Decision-Making Process in the Treatment of Kienböck's Disease - Tee, Richard; Butler, Stephen; Ek, Eugene T.; Tham, Stephen K. (Journal of Wrist Surgery, 2024)
Background In recent years, the classification and treatment algorithm for adult Kienböck's disease (KD) has expanded. However, the priority of the investigations done in determining its management has not been discussed, as not every patient with KD requires magnetic resonance imaging (MRI) or wrist arthroscopy.Materials and Methods We discuss the role of these investigations and emphasize the importance of computed tomography (CT) imaging in evaluating the cortical integrity of the lunate and its role in the decision-making process and management of KD.Results We put forward an investigative algorithm that places into context the investigative roles of MRI, arthroscopy, and CT.Conclusion KD is a rare condition, and there is a lack of comparative studies to help us choose the preferred treatment. The decision on the management options in adult KD may be made by determining the integrity of the lunate cortex and deciding whether the lunate is salvageable or not by CT scan. MRI may provide useful information on the vascular status if the lunate cortex is intact, and the lunate is salvageable. If the lunate is fragmented, it is not salvageable, and MRI does not provide useful information. Arthroscopy has a role in selective cases.
Keywords: Kienböck disease; imaging; classification